Visual attention to the main image of a hotel website based on its position, type of navigation and belonging to Millennial generation: an eye tracking study - Espigares-Jurado, Francisco (2021)
This article focuses on the role played by the images that hotels use on their websites. Under this approach, this study analyses the main image used in a hotel website, considered an area of outstanding interest, which can help to improve the first impression when arriving at the website and, with it, increase the number of bookings. The absence of studies on this matter aroused the interest in it. The proposed experiment allows to check how these images influence the pattern or metrics of visual attention of users as well as their cognitive processing. The eye tracking technology was chosen with the intention of knowing several aspects of this fixation behaviour according to: the position of the image on the website, whether or not it belongs to the Millennial generation and the type of navigation it performs (exploratory vs. goal oriented), in addition to proposing some interaction effects between these classification variables studied. The results achieved revealed that an image in the upper area of a website is more effective, but there are some differences in the visual attention among groups of participants. This attention to it will depend, in part, on the type of task to be carried out within the website and the user age. Specifically, goal-oriented users showed a lower recurrent interest in the main image. The fixation was shorter in the group belonging to the Millennial generation, who do not need, given their greater experience in the web, a longer time to process the cognitive load of the image. Although the hypotheses proposed on the basis of the literature are not entirely satisfactory, the present study allows laying the foundations for more complex future works.